Recording and management of Byzantine and post Byzantine monuments in central Messenia - Παναγόπουλος, Νικόλαος (Πανεπιστήμιο Πελοποννήσου, 2019)
The first Christian community was spotted in Messenia in Koroni, with the foundation of a large early Christian basilica dated back at the 5th century. From this time began the period of christianization of the population. In this thesis the Byzantine churches of the area north of the village of Androusa till the village of Polixni will be presented and examined. Twenty-nine (29) Byzantine and Post Byzantine monuments will be presented. An analytical review of the architecture, history and chronology is given, based on references information, while the problems and solutions for their management wil be presented. The reason for the selection of this study area is, because it was spotted a lack of references information and archaeological research in this specific region. The scope of this thesis is to record, detect, analyze and recognize the problems, and give solutions concerning the Byzantine monuments. At the beginning of the thesis the historical frame will be given focused mainly in the Byzantine periods. Then, the Byzantine churches will be analyzed. Most of the monuments were visited and an approach of the problems of the monuments will be given, in order to extract possible solutions for the management and preservation of the monuments based on new technologies. The study area has a high number of important Byzantine churches, both known and unknown to the scientific community. Further investigation for the preservation and protection of the sites is necessary for the Byzantine Heritage of Messenia.
Keywords: Εκκλησίες -- Ελλάδα -- Μεσσηνία; Εκκλησιαστική αρχιτεκτονική -- Ελλάδα -- Μεσσηνία; Ορθόδοξη Ανατολική Εκκλησία -- Ελλάδα -- Μεσσηνία -- Ιστορία; Εκκλησιαστική αρχιτεκτονική -- Συντήρηση και αποκατάσταση -- Ελλάδα -- Μεσσηνία; Μεσσηνία (Ελλάδα) -- Κτήρια, κατασκευές κ.λπ.; Βυζαντινές Εκκλησίες; Μεσσηνία; Ιστορία; Αρχιτεκτονική; Συντήρηση και αποκατάσταση